The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1046/j.1440-1843.2000.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Air quality in Malaysia: Impacts, management issues and future challenges

Abstract: The general air quality of Malaysia since 1970 has deteriorated. Studies have shown that should no effective countermeasures be introduced, the emissions of sulfur dioxide, nitrogen oxides, particulate matter, hydrocarbons and carbon monoxide in the year 2005 would increase by 1.4, 2.12, 1.47 and 2.27 times, respectively, from the 1992 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 0 publications
4
66
1
2
Order By: Relevance
“…These states, as well, held the largest number of outbreaks of fire during the study period. Further research [11][12][13][14] found similar occurrences with fire burning in Asia and an association with an increase in hospitalizations for asthma and other respiratory illnesses. Though, higher rates in the period may be explained by the decrease in relative humidity during this season and the consequent increase in the amplitude between maximum and minimum temperatures 27 .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These states, as well, held the largest number of outbreaks of fire during the study period. Further research [11][12][13][14] found similar occurrences with fire burning in Asia and an association with an increase in hospitalizations for asthma and other respiratory illnesses. Though, higher rates in the period may be explained by the decrease in relative humidity during this season and the consequent increase in the amplitude between maximum and minimum temperatures 27 .…”
Section: Discussionmentioning
confidence: 83%
“…In 2007, the Amazon reported admissions in the elderly population totaling 157 055 in the SUS, with asthma accounting for 3 554 (2.3%) 8 . Specific studies on forest burning in Asia have shown an increased incidence of asthma and acute respiratory infections (ARI) [11][12][13][14] in those areas. Studies in the Southeast have also shown an increasing trend in hospitalizations for asthma and other respiratory diseases related to biomass burning in urban areas [15][16][17][18] , with a greater frequency of hospitalization for respiratory diseases in the dry season for various age groups [19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…According to Muraleedharan et al (2000a) many Southeast Asian haze episodes, such as those recorded in 1983, 1990, 1991, 1994, 1997 and 1998, have resulted in negative health effects on a large population. Suspended particles from haze in particular can impact human health in a number of ways, leading to conditions such as upper respiratory tract infection, asthma, and conjunctivitis (Awang et al, 2000). In addition, the release of organic pollutants from biomass burning, such as PAH which is carcinogenic, can lead to a high risk of cancer (Tullin et al, 2001;Silva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Meteorological conditions, particularly atmospheric stability and wind speed, might have caused the late evening peak from the diurnal variation (Afroz et al, 2003;Awang et al, 2000;Azmi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%